PENURUNAN NYERI DAN PENINGKATAN MOBILITAS FISIK PASIEN PASCA KISTEKTOMI ENDOMETRIOSIS: CASE STUDY - Intani, Merlisa Kesuma; Saputra, Dikki; Harmita, Devi; Luthfiati, Nur (Jurnal Keperawatan dan Kesehatan, 2025)
This case report aims to describe the holistic nursing care provided to three patients following cystectomy surgery due to Endometriosis. The three subjects, Mrs. E (33 years old), Mrs. F (30 years old), and Mrs. G (35 years old), were admitted on the first postoperative day with chief complaints of Acute Pain and Impaired Physical Mobility. Assessment revealed that Mrs. E experienced Acute Pain with a score of 8 on the surgical incision site, required total bed rest, and had elevated Leukocyte levels (15,600/µL). Similar findings in Mrs. F and Mrs. G also indicated acute pain of high intensity and immobility. The primary nursing diagnoses established for all three cases were Acute Pain (D.0077), Impaired Physical Mobility (D.0054), and Risk for Infection (D.0147). Interventions focused on non-pharmacological pain management (deep breathing technique) and gradual early mobilization. Following 3x24 hours of nursing implementation, a significant decrease in pain intensity was observed (Mrs. E's pain decreased from a score of 8 to 3) and an improvement in mobility ability was noted in all three cases. The integrated nursing interventions demonstrated a positive effect on reducing pain and enhancing the functional mobility of the postoperative patients.